Design and Analysis of Heterojunction Tunneling Transistor (HETT) based Standard 6T SRAM Cell - Satyanarayana, B. V. V.; Durga Prakash, M. (International Journal of Engineering and Technology, 2018)
Subthreshold Swing (SS) of MOSFETs, which determines the low voltage operation of portable mobile devices, cannot reduce below 60mV/dec that restricts MOSFETs for ultra-low power applications. This work presents design and implementation of high ON current, improved Miller capacitance and reduced Subthreshold Swing heterojunction tunneling transistors (HETTs) for portable electronic systems. The performance of HETT with MOSFET has been compared. In this work, the overlapping of gate/oxide on to source can increase the band to band tunneling (BTBT) and improves the ON current of the transistor. Miller capacitance effect can be reduced by the use of low band offset materials and low energy states of materials like Ge or SiGe. This, in turn, results in better performance characteristics for the transistor.The Proposed design and implementation of HETT include both N-type HETT (NHETT) and P-type HETT (PHETT) fabrications and the performance characteristics analysis of both NHETT and PHETT are provided. The advantages and limitations of both NHETT and PHETT for beyond CMOS technologies, in addition to the basic and structural differences between HETTs and conventional MOSFETs to facilitate the use of HETT in place of MOSFET have been elaborated in detail. The construction process of HETT is not at all completely different which is suitable to MOS Design process and is applicable for portable mobile applications. The power analysis of HETT based standard 6T SRAM cell is provided and the performance is verified with the conventional MOSFET based 6T SRAM cell.Â Â